Impact of Smoking Behavior on Learning Achievement : A Case Study at PGRI Bandongan Junior High School Students - Tugastono Taufiq (Universitas Muhammadiyah Yogyakarta, 2023)
Academic restoration is the result of student learning obtained from learning activities in schools or colleges that look at cognitive aspects, and academic achievement is generally determined through measurement and assessment. Learning achievement is influenced by several factors, one of which is smoking behavior. The impact of cigarette smoke itself triggers the brain, which makes a person weak in thinking power. Early adolescent smoking will have a significant impact on teaching and learning activities if allowed to continue. This study aims to determine the impact of smoking behavior on student learning achievement. This research design uses quantitative research types with correlational designs, questionnaires, and report card values or cumulative achievement indices as data collection tools. Research variables include smoking behavior as a free variable and learning achievement as a bound variable. From the results of the study, it showed that there was no significant influence of smoking behavior on student learning achievement at SMP PGRI Bandongan. After achieving an R-squared value of 0.227, the researcher Therefore, the influence of smoking on student learning achievement at SMP PGRI Bandongan is 22.7%. In the simple linear regression test, it is known that F count = 49.560 with a significance rate of 0.224 > 0.05, therefore there is no influence of the smoking behavior variable X on the learning achievement variable Y.